Neo-Eskimo Occupations of the Northern Labrador Coast - Kaplan, Susan A. (ARCTIC, 1980)
Archaeological and historical information are brought together in an examination of the changing economic and social interaction spheres of the Labrador Neo-Eskimo from the Thule period through the 19th century. Animal availability, hunting technologies and strategies, and direct and indirect contact between Neo-Eskimos and various European groups are considered in a discussion of changing subsistence practices and settlement patterns. The paper pin-points a pattern of intensification and eventual disintegration of cooperative endeavours between Neo-Eskimo groups inhabiting northern Labrador.